Betrayal of the blood lily [compact disc, unabridged] - Willig, Lauren (Willig, Lauren. Pink carnation series., 2010)
As Lady Frederick Staines, Penelope Deveraux plunges into the treacherous waters of the court of the Nizam of Hyderabad. With the assistance of Captain Alex Reid she draws out the deadly plans of the spy known as the Marigold.